Effect of alkali treatment on interfacial and mechanical properties of kenaf fibre reinforced epoxy unidirectional composites - Ren, Zilong; Wang, Chunhong; Zuo, Qi; Yousfani, Sheraz Hussain Siddique; Noor Intan Saffinaz Anuar,; Sarani Zakaria,; Liu, Xiaoling (Penerbit Universiti Kebangsaan Malaysia, 2019)
Kenaf fibres demonstrate enormous potential in fibre reinforced composites with the excellent performance and environmental benefits. In this work, kenaf fibres were treated with NaOH at the concentrations of 1%, 2%, and 3%. Effects of the alkaline treatments on the mechanical properties of fibre and interfacial shear properties (IFSS) of the resulted composites were systematically evaluated. In addition, relationship between tensile strength and surface friction coefficient of kenaf fibre was shown. Relationship between tensile strength of fibre and IFSS of composites were explored. They were conducted by correlation analysis method. The results indicated that after NaOH treatment, kenaf fibres has increased in tensile strength, surface roughness, friction coefficient, but decreased in diameter. Tensile properties, flexural properties and water absorption of unidirectional kenaf fibre reinforced epoxy resin composites have improved. IFSS of composite treated at 2% alkali has increased by 10.34%, compared to composites untreated fibres. Correlation analysis indicated that there was no significant correlation between kenaf fibre tensile strength and IFSS of the composite. On the other hand, there was significant correlation between kenaf fibre surface friction and the IFSS of the composite with the correlation coefficient of 0.905.